Accès de la femme paysanne Turumbu au foncier et sa participation à la sécurité alimentaire en contexte de changement climatique dans une zone de transition à la Réserve de Biosphère de Yangambi (RDC). Expérience du village Lilanda en Province de la Tshop - LIKAKA Angowakololo M; ESISO Asia-Amani. F; WELEPELE Elatre C; MUANASAKA KabuitaL (IJRDO - Journal of Social Science and Humanities Research, 2021)
Agriculture is particularly important and constitutes the backbone of almost all African national economies. In the DRC, agriculture employs more than 70% of the active population and contributes more than 60% to job creation. It is the main source of food for households and is therefore a key element for household food security. Women, who are, however, the main actors of agriculture and family food security, unfortunately remain marginalized by certain customs, as for their access to land. This state of affairs is complicated by the effects of climate change on agricultural activities. In order to understand how women access land and how this access affects their participation in efforts to maintain food security in the context of climate change, we began this study at the Biosphere ReserveYangambi in the village of Lilanda. To properly address this problem, we conducted 105 individual interviews with the residents of Lilanda. The gender approach was a priority and we wanted to have a lot of women among our respondents. Interviews were conducted with 68 women (65% of respondents) and 37 men (35% of respondents). The data from these interviews were processed using the R software and assisted by Excel 2013. The results show that the contribution of women to food security is perceptible as indicated by the answer given by all our respondents (100%). There is a regulation regulating access to land (70%) and 60% of our respondents recognize that this regulation is favorable to women. The people of Lilanda say that custom is not a barrier to women’s access to land, according to 90% of our respondents. All women, without exception, have the right to access the land in the same way men. Divorced women and those living alone have much easier access to land than married women who are dependent on their husbands. Climate change has an impact on food security in Lilanda, as 97% of this population is said to have been hit by investigators. This change is reflected in seasonal disturbances (47.62%), production decline (25.71%) and crop wilting (22.86%). The majority of the population (43.81%) do not know what to do with these climatic disturbances. Some prefer to combine crops in fields (14.29%), others prefer to substitute crops that do not adapt (12.38%) to this context.